Codzienność szkolna dzieci ze specyficznym zaburzeniem językowym (SLI) - Kamińska, Sofia (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
In this article the author raises the problem of everyday school life of children with specific language impairment (SLI), marked by social exclusion. Specific language impairment is defined today as improper language acquisition by children who were not diagnosed with brain structure damage, hearing impairment or impairment of learning processes. The children were not also devoid of contacts with the surrounding. SLI affects approximately 7% of the population of children. The daily life of children with SLI because of the difficulty with verbal communication is marked by permanent stress, deprivation of basic psychological needs, rejection by peers and lack of support from teachers. Children with SLI experience in educational numerous setbacks, which translates into lack of success at school and exclusion from the peer group. The author suggests a solutions that could help to improve the situation of student with SLI.
Keywords: grupa rówieśnicza; niepowodzenia szkolne; SLI; specyficzne zaburzenia językowe; wykluczenie społeczne